The Concept of Counseling Implementation in Islam - Wahyudi, Ahmad; Mukarromah, Kamilatul; Mahmudah, Mahmudah (Al Irsyad: Jurnal Studi Islam, 2023)
Islamic religious counseling is essential for enhancing the public’s understanding, morality, and piety toward Islamic teachings amid complex and dynamic global and social changes. This study aims to systematically describe the concept of counseling in Islam, starting from the pre-counseling stage, the counseling process, to the post-counseling stage. The research method uses a descriptive qualitative approach through a literature study. Data collection techniques include documentation studies, and data processing involves reduction, data presentation, and conclusion drawing. Research findings: Pre-Counseling: A planning stage that includes identifying the target audience (mad’u), determining language style, counselor’s appearance, selecting material, methods, media, and preparing the counselor’s mental readiness. Counseling Process: The implementation phase begins with greetings, sincere intention, sending blessings (shalawat), and delivering the material in a polite manner, incorporating humor, and avoiding coercion. Post-Counseling: The evaluation stage, assessing the alignment between implementation and planning, as well as collecting feedback from the mad’u for improvement. Conclusion: The concept of Islamic counseling includes the pre-counseling, process, and post-counseling stages, emphasizing planning, respectful implementation, and feedback-based evaluation.